The personal fonds of Grigory Chooduevich Shirshin at the National Archives of the Republic of Tuva - Archimaeva, Aleksandra I. (The New Research of Tuva, 2022)
The article presents an analysis of the documents of the personal fonds of a statesman of Tuva in the Soviet period — the first secretary of the Tuvan Regional Party Committee (1973–1990), Chairman of the Great Khural (1995–1998), deputy of the Supreme Khural of the Republic of Tuva (1998–2002) Grigory Chooduevich Shirshin (born in 1934). This fonds is kept in the National Archives of the Republic of Tuva. The documents were accepted for storage on December 25, 2019 from the holder of the archive. The personal fonds contains 120 items, including an autobiography, documents on official business, creative documents, as well as other records collected by G. Ch. Shirshin himself on topics of interest to him. By using these documents, it is possible to trace all his work activities, as well as his creative works and academic publications. Official letters of verification, programs, etc. allow us to analyze the development of the national economy of Tuva during this period. The personal archive of G. Ch. Shirshin can become one of the most important sources for research into the Soviet period of the history of Tuva, issues of its management and strategic development.